Using the Structure‐Function Linkage Database to Characterize Functional Domains in Enzymes. Issue 1 (12th December 2014) - Brown, Shoshana; Babbitt, Patricia
Abstract: The Structure‐Function Linkage Database (SFLD; http://sfld.rbvi.ucsf.edu/ ) is a Web‐accessible database designed to link enzyme sequence, structure, and functional information. This unit describes the protocols by which a user may query the database to predict the function of uncharacterized enzymes and to correct misannotated functional assignments. The information in this unit is especially useful in helping a user discriminate functional capabilities of a sequence that is only distantly related to characterized sequences in publicly available databases. © 2014 by John Wiley & Sons, Inc.